PENERAPAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA PADA MATAKULIAH PROBLEMATIKA LINGKUNGAN HIDUP - Al Muhdhar, Mimien Henie Irawati (Universitas Sebelas Maret, 2014)
The research titled the Implementing of Contextual Teaching andÂ Learning to Improve of the Critical Thinking Skills of the Students in the Subject of Environmental Problematics have done in 2013. This study generally aims to improve students' critical thinking skills in the subject environmental problematic. The critical thinking skills consist of skills to formulate the problem statement, analyze the argument, questioning and answering, evaluating of information source credibility, observation skill, and the skills of interact with the others. This research is classified as classroom action research carried out in two cycles. Every cycles consist of planning, implementing, observing, and reflecting. The result showed that the CTL is able to increase the critical thinking skills of the students on the subject of environmental problematics. We recommended that CTL should be apply in the other subject with the same characteristic like environmental knowledge, advancer ecology, environmental pollution, etc.Â Keywords:CTL, critical thinking, environmental problematics